Efficiency benchmarks in the surgical management of primary rhegmatogenous retinal detachment: a monocentric register cohort study of operating room time metrics and influential factors - Claus Zehetner; Martina T Kralinger; STEFAN EGGER; Yvonne Nowosielski; Reinhard Angermann; Anna Lena Huber; Markus Hofer (BMJ Open, 2021)
Objectives To investigate the effect of clinical, methodological and logistic factors on operating room (OR) efficiency in the surgical management of primary rhegmatogenous retinal detachment (RRD).Design Monocentric retrospective register cohort study.Setting Single tertiary centre in the western region of Austria.Participants We audited patients diagnosed with primary RRD who were treated between January 2014 and August 2019. In total, 783 eyes of 776 consecutive patients were included in this study. Various risk factors affecting OR time efficiency and anatomical success after pars plana vitrectomy (PPV) procedures and scleral buckle (SB) surgery were analysed.Primary and secondary outcome measures OR efficiency was the primary outcome measure. Secondary outcome measures were the primary success rate after PPV procedures and SB surgery.Results PPV was performed in 641 (81.9%) eyes and SB surgery in 142 (18.1%) eyes. Mean surgical times in PPV and SB under retrobulbar anaesthesia (RA) were 74.0 (±32.6) min and 62.1 (±24.6) min (p<0.001), respectively, while under general anaesthesia (GA), these values were 112.0 (±52.0) min and 76.0 (±22.5) min (p<0.001), respectively. A regression analysis revealed the following main risk factors for prolonged OR time for the surgical management of RRD with PPV (all p<0.001): presence of a giant tear (β=24.01; 32%), proliferative vitreoretinopathy (PVR)-C (β=16.43; 22%), surgery postponed for 72 hours after diagnosis (β=21.40; 29%), GA (β=23.64; 32%) or surgery performed by a trainee (β=17.35; 23%). PVR (p=0.022) in PPV cases, after-hours settings (p=0.006) and surgeon experience (p=0.030) in SB cases were independent risk factors for reduced success rates.Conclusions OR coordinators should consider various independent clinical (giant tear, PVR-C, advanced detachment), methodological (PPV vs SB) and logistic (GA vs RA, after-hours setting and surgeon experience) factors to improve the success rate and surgical management planning of RRD accurately while optimising OR resources and staff efficiency.